The Relationship of Heart Rate Recovery Post Exercise Stress Test To Syntax Values In Patients With Stable Coronary Artery Disease - Iskandar, Iskandar; Anjarwani, Setyasih; Tjahjono, Cholid Tri; Satrijo, Budi; Swastika Putri, Valerinna Yogibuana (Universitas Brawijaya, 2022)
Background:The prognostic usefulness of abnormal heart rate recovery (HRR) as a predictor of death has been discovered. Abnormal HRR results from inadequate vagal activation after exercise. The association between HRR and angiography in CAD (coronary artery disease) has been studied, however the conclusions are still being contested due to a lack of data. The purpose of this study is to see if HRR after an EST (exercise stress test) may predict the severity of syntax values in individuals with stable CAD at Saiful Anwar Hospital Malang (RSSA). Methods:This study is an analytic observational study with a retrospective cross sectional design. It was held in Saful anwar, Malang Hospital during January 2017–December 2019, including 366 patients. All patients underwent exercise stress test for CAD screening and coroner angiography. Those were divided into two groups, which included syntax score < 23 (n=148) and syntax score ≥ 23 (n= 218). Result: Chi-square analysis was used to analyze the relationship correlation between HRR1, HRR2 and Syntax Score, and was used to compared between HRR1 (heart rate recovery first minutes), HRR2 (heart rate recovery second minute) and Syntax Score group. The confounding factor was adjusted with multivariate logistic regression analysis and AUC curve. There was a significant negatif correlation between abnormal HRR1 and HRR2 after exercise and Syntax score, with strong correlation (HRR1 ; OR = -2.11, p = 0.00 AUC :90,8%, HRR2 ; OR = -1,6, p = 0,48, AUC : 70,4%). Conclusion: Abnormal first and second minutes of HRR after exercise stress test in stable CAD patient have a higher incidence of high Syntax Score (>1) than stable CAD patient with normal HRR. Keywords: Coronary artery disease (CAD), Heart rate recovery (HRR), Syntax.